Effects of Monochromatic Lighting During Incubation and Vaccination on the Splenic Transcriptome Profiles of Chicken - Ibrahim, Mohamed M. A.; Nelson, Jill R.; Archer, Gregory S.; Athrey, Giridhar (Frontiers in Genetics, 2021)
Lighting is a crucial environmental variable in poultry operations, but illumination during incubation are relatively understudied. The ability to stimulate development or immune performance using in ovo lighting is a promising approach for improving poultry health and welfare. This study investigated how monochromatic green light during incubation and vaccination method and timing affected chicken splenic gene expression patterns. We performed this study with 1728 Hy-Line white layer eggs incubated under two light treatments during incubation: continuous dark and continuous green monochromatic light, over the entire incubation period. Half the eggs in each light treatment received in ovo vaccination, applied on embryonic day 18 (ED18). The remaining half were vaccinated by spraying on hatch day. After hatch, the light treatments followed the industry-standard lighting regimens. The study had six treatment groups with light-dark pairs for non-vaccinated, in ovo vaccinated, and post-hatch vaccinated. We assessed splenic gene expression at ED18 and at seven days post-hatch (PH) in all the treatments. We isolated and sequenced twenty-four mRNA libraries on the Illumina platform, followed by bioinformatics and differential gene expression analyses. RNAseq analysis showed between 62 and 6755 differentially expressed genes (DEG) between comparisons, with the most prominent differences observed between ED and PH samples, followed by comparisons between vaccination methods. In contrast, light vs. dark treatments at ED showed limited effects on transcriptomic profiles. However, we observed a synergistic effect of lighting during incubation on post-hatch vaccination responses, with differentially expressed genes (DEG) unique to the light treatment showing stimulation of cell proliferation with significance for immune activity (inferred from gene ontology terms). Gene ontology and pathway analysis indicated biological processes like cellular component organization or biogenesis, rhythmic process, developmental process, response to stimulus, and immune system processes were explained by the DEG. While lighting is an important source of circadian stimulation, other controlled studies are required to clarify whether in ovo circadian entrainment plays a role in modulating immune responses.